2017
DOI: 10.4103/0366-6999.213965
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers for Chronic Kidney Disease with a Focus on Gene Transcript

Abstract: Objective:In the upcoming era of precision medicine, searching for the early, noninvasive biomarkers has been the cornerstone and major challenge in the management of chronic kidney disease (CKD). Urine contains rich biological information which could be the ideal source for noninvasive biomarkers of CKD. This review will discuss the recent advance in urinary biomarker.Data Sources:This review was based on data in articles published in the PubMed databases up to June 20, 2017, with the following keywords: “Chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
12
0
2
Order By: Relevance
“…Despite compelling examples of the use of genomics to support personalized medicine, genomics alone is unlikely to provide sufficient information regarding disease pathophysiology and prognosis. Indeed, in spite of other omics approaches, including transcriptomics and metabolomics, have emerged as powerful tools for developing novel biomarkers for CKD in recent years [86][87][88] , and proteomics remains the classic realm for biomarker discovery. In this respect, transcriptional, translational, and post-translational modifications, which cause functional changes to proteins and their function, represent another unexplored area.…”
Section: Towards Personalized Medicine: Future Prospects and Challengesmentioning
confidence: 99%
“…Despite compelling examples of the use of genomics to support personalized medicine, genomics alone is unlikely to provide sufficient information regarding disease pathophysiology and prognosis. Indeed, in spite of other omics approaches, including transcriptomics and metabolomics, have emerged as powerful tools for developing novel biomarkers for CKD in recent years [86][87][88] , and proteomics remains the classic realm for biomarker discovery. In this respect, transcriptional, translational, and post-translational modifications, which cause functional changes to proteins and their function, represent another unexplored area.…”
Section: Towards Personalized Medicine: Future Prospects and Challengesmentioning
confidence: 99%
“…Each year, CKD affects millions of people from all backgrounds and nations [2]. One of the problems associated with CKD is that, there are no early clinical symptoms to be used for diagnosis before the kidney enters an irreversible functional stage [3]. CKD also increases risk of cardiovascular diseases, hospitalization, and mortality [2, 4].…”
Section: Introductionmentioning
confidence: 99%
“…27600) commercially [2]. Recently, four clinical markers have been reported for diagnosis of IgAN (or for differential diagnosis of the disease from the other types of primary chronic glomerulonephritis); which are as follows: [1] > 5 RBCs/HPF in urinary sediments, [2] persistent proteinuria (urinary protein > 0.3 g/d), [3] a serum IgA level of > 315 mg/dl, and [4] a serum IgA/C3 ratio of > 3.01 [2]. Chan, et al found that, IC deposition in mesangial region leads to secretion of Tumor Necrosis Factor-α (TNF-α) by mesangial cells; they also found that, inflammatory changes occur in renal interstitium [2, 54].…”
Section: Introductionmentioning
confidence: 99%
“…The continued development of CKD results in the increased risk of cardiovascular (CV) disease and may even lead to sudden cardiac death and heart failure . The major challenge of the CKD treatment is that there were no early clinical symptoms before CKD develops to the irreversible damage phase . Therefore, it is urgent to find candidate biomarkers to predict and control the progression of CKD …”
Section: Introductionmentioning
confidence: 99%
“…5 The major challenge of the CKD treatment is that there were no early clinical symptoms before CKD develops to the irreversible damage phase. 1 Therefore, it is urgent to find candidate biomarkers to predict and control the progression of CKD. 6 According to recent studies, in the kidney, different microRNA (miR) expression in the courses of acute kidney injury (AKI) and CKD development in humans and experimental rodent models has been found through high-throughput screening techniques, like microarray and small RNA sequencing.…”
mentioning
confidence: 99%